Josef Bernard (ed.), Tomáš Kostelecký, Renáta Mikešová, Jiří Šafr, Martin Šimon, Lucie Trlifajová, Jakob Hurrle: Nic se tady neděje… Životní podmínky na periferním venkově - Hudečková, Helena (Lidé města, 2019)
A review of the book by Josef Bernard (ed.).